Development and validation of female hedonic orientation scale - Teo, Carol Boon Chui; Md Sidin, Samsinar (Elsevier, 2014)
This paper seeks to develop and validate a Female Hedonic Orientation Scale (FHOS). Methodology utilized mixed method to elicit women's perception and opinions towards hedonic orientation. Initial item generation involved two focus group sessions on female respondents. Findings from focus groups revealed that hedonism is a personal value with extraversion characteristics such as female's propensity to be sociable, active, pursuit of challenge and excitement-seeking. The 8-item FHOS was purified using survey questionnaire approach on 444 female samples. Structural Equation Modelling using exploratory and confirmatory factor analyses were employed to evaluate goodness-of-fit of the measurement construct. Reliability and validity tests were undertaken to test robustness of the scale.